Increased Lymph Node Yield Is Associated With Improved Survival in Rectal Cancer Irrespective of Neoadjuvant Treatment: Results From a National Cohort Study. Issue 9 (September 2015) - Lykke, Jakob; Jess, Per; Roikjaer, Ole
Abstract : BACKGROUND: It has been proposed that the lymph node yield achieved during rectal cancer resection is associated with survival. It is debated whether a high lymph node yield improves survival, per se, or whether it does so by diminishing the International Union Against Cancer stage drifting effect. OBJECTIVE: The purpose of this study was to evaluate the prognostic implications of the lymph node yield in curative resected rectal cancer. DESIGN: This study was based on data from a prospectively maintained colorectal cancer database. SETTINGS: This was a national cohort study. PATIENTS: All 6793 patients in Denmark who were diagnosed with International Union Against Cancer stage I to III adenocarcinoma of the rectum and so treated in the period from 2003 to 2011 were included in the analysis. MAIN OUTCOME MEASURES: The primary outcome measure was overall survival. RESULTS: The observed percentages of patients with International Union Against Cancer stage III disease with a lymph node yield less than 12 or 12 or more were 28.1 % and 40.7% ( p < 0.0001) in the non-neoadjuvant treatment group and 26.9% and 38.3% ( p < 0.0001) in the neoadjuvant treatment group. The 5-year overall survival rates for patients with a lymph node yield <12 or 12 or more were 73.1% and 80.6% in International Union Against Cancer stages I to II ( p < 0.0001) and 57.4% and 53.3% in stage III ( p < 0.142) in the neoadjuvant treatment group and 70.4% and 79.2% in stages I to II ( p < 0.0001) and 46.6% and 59.1% in International Union Against Cancer stage III ( p < 0.0001) in the non-neoadjuvant treatment group. In multivariate analysis, the lymph node yield turned out to be an independent prognostic factor, irrespective of neoadjuvant treatment. LIMITATIONS: It is not possible in an observational study to tell whether the findings are associations rather than causal relationships. CONCLUSIONS: Increased lymph node yield was associated with better overall survival in rectal cancer, irrespective of neoadjuvant treatment. Stage migration was observed.